Gut mycobiome and its interaction with diet, gut bacteria and alzheimer's disease markers in subjects with mild cognitive impairment: A pilot study - Nagpal, Ravinder; Neth, Bryan J.; Wang, Shaohua; Mishra, Sidharth P.; Craft, Suzanne; Yadav, Hariom (EBioMedicine, 2020)
Recently, we reported that patients with mild cognitive impairment (MCI) harbor specific signature of bacteria in their gut and that a modified Mediterranean ketogenic diet (MMKD) improves Alzheimer's disease (AD) markers in cerebrospinal fluid (CSF) and the signatures of gut bacteria. However, other microbial population such as gut fungi (mycobiome) in relation to MCI/AD pathology, gut bacteria and diet remain unknown. We measure gut mycobiome by sequencing of the fungal rRNA ITS1 gene in 17 older adults (11 MCI; 6 cognitively normal [CN]) in a single-center, randomized, double-blind, crossover pilot study, before and after 6 weeks intervention of MMKD and American Heart Association Diet (AHAD), and determine its correlation with AD markers in CSF and gut bacteria. Compared to CN counterparts, patients with MCI have higher proportion of families Sclerotiniaceae, Phaffomyceteceae, Trichocomaceae, Cystofilobasidiaceae, Togniniaceae and genera Botrytis, Kazachstania, Phaeoacremonium and Cladosporium and lower abundance of Meyerozyma. Specific fungal taxa exhibit distinct correlation arrays with AD markers and gut bacteria in subjects with versus without MCI. MMKD induces broader effect on fungal diversity in subjects with MCI and increases Agaricus and Mrakia while decreasing Saccharomyces and Claviceps with differential response in subjects with or without MCI. The study reveals MCI-specific mycobiome signatures and demonstrates that distinct diets modulate the mycobiome in association with AD markers and fungal-bacterial co-regulation networks in patients with MCI. The findings corroborate the notion of considering gut mycobiome as a unique factor that can affect cognitive health/AD by interacting with gut bacteria and diet and facilitate better understanding of the AD and related microbiome, using unique diet or microbiome modulators. [Display omitted]